Structural Components of Cognitive Rigidity - A.N. Pevneva (Экспериментальная психология)
The introduction describes the object of the study - cognitive rigidity. The purpose of the study is to identify the component composition of cognitive rigidity through the processes of switching, interference and control. Presumably, cognitive rigidity is not a unitary construct and has its own structure including the processes of switching, interference and control. The results of the study of cognitive rigidity within the framework of three approaches are discussed: cognitive rigidity as interference (J. Stroup), as switching and cognitive control (A. Lachins). The study was conducted in 2 stages: the participants of the first stage were 584 respondents (M = 21.46; SD = 6.22); the participants of the second stage were 204 (M = 19.66; SD = 5.06). A series of samples included in the test of J. Stroup, the method “Study of the influence of past experience on the way of problem solving” and “Lability of thinking” by A. Lachins, reflecting the processes of switching, interference and control, were conducted. The study revealed statistically significant differences between the indicators of variables within each technique. Within the framework of correlation analysis, intercorrelations between the scales within each technique were recorded, indicating the unity of interference, switching and cognitive control. At the same time, the differentiated nature of correlations between the parameters of all variables indicates the difference in measurement procedures. Within the framework of factor analysis, cognitive rigidity breaks down into a number of components, which allows us to assume its heterogeneity and to set the task of differentiating cognitive rigidity taking into account its structures. The results of the study contribute to supplementing the previously developed general model of rigidity, and can also be applied to the study of cognitive rigidity.